Penerapan Dan Pelatihan Mesin Penyangrai Kacang Kawangkoan Pada Ikm Rimawar Kabupaten Minahasa: Application and Training of Kawangkoan Peanut Roaster Machine at IKM Rimawar of Minahasa Rigency - Pomalingo, Moh Fikri; Fatimah, Feti; Gede Suarjana, I Wayan (Departemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Kawangkoan beans are well known as one of the souvenirs and snacks typical of North Sulawesi. Named kawangkoan beans, because the area has a fertile soil type and a climate suitable for peanut growth. Kacang is also an icon of the Kawangkoan sub-district which has been enshrined in a peanut statue. The manufacture of kawangkoan beans is usually carried out in several stages, namely from upstream to downstream processes. The stages of making kawangkoan beans sequentially include planting, fertilizing, caring, harvesting, drying, roasting, packaging, and selling. These stages are usually carried out by several farmer groups and home industries, especially IKM Rimawar. The purpose of this service is to implement and train partners regarding the kawangkoan bean roasting machine so that later roasted peanut production is better, faster and cost-effective. The methodology carried out includes field surveys, interviews, machine manufacturing, training, machine handover and reporting. The results obtained from this service are that participants are able to understand the process of using and maintaining machines with a percentage of 95%. In addition, for the percentage of participant activity, this value reaches 90%. The activity was obtained from the observations of the participants during the training. Furthermore, for the cooperation process, all participants were able to work well together, this was shown by the percentage of group cooperation which reached 95%. The application of this peanut roaster machine is very good for partners and easy to use. Used fuel oil is easy to find, making the use of this machine able to protect the environment from indiscriminate disposal of used oil waste.